APPLICATION OF COGNITIVE THEORY IN OVERCOMING PROCRASTINATION AGAINST STUDENTS - Syifa Awaliyah Nurrohmah; Mamat Supriatna (Universitas Pendidikan Indonesia, 2024)
The procrastination behavior experienced by students is very disturbing, which can negatively affect students' lives. There are several research findings regarding the application of counseling services to overcome procrastination with various cognitive theory treatments. This research was conducted using a systematic literature review (SLR) method. The steps in carrying out the SLR method are by compiling statements related to the research carried out, conducting searches with systematic literature reviews, identifying, assessing, analyzing, and compiling reports.